Aspectos da biologia da carapeba-listrada, Eugerres brasilianus (Cuvier, 1830), no sul da Bahia: uma abordagem a partir de análises de otólitos e de séries temporais, capturas e esforço da pesca artesanal - Santana, Camila Brito de (2023)
Understanding aspects of population dynamics is relevant, as the parts obtained through these analyzes are useful for the appropriate management of species, including those captured from fishing. Knowledge about aspects such as age, growth and reproduction of species guides strategies for restricting fishing in reproductive periods or critical phases of the life cycle. To analyze age and growth parameters, readings from calcified structures such as otoliths are used, which offer biological contributions to the individual's longevity, age at first maturation and growth rates. From interpretations and quantifications of the rings present in its structure, it is possible to understand, together with the population dynamics of the species, temporal variability, seasonal dynamics, episodic events and long-term trends. Among the species explored and relevant to artisanal fishing, Eugerres brasilianus, popularly known as carapeba-striped, stands out. However, scientific knowledge about its biology and population ecology is still little explored. Therefore, it is necessary to understand the population structure of this species in terms of age and growth criteria based on otolith analyses, for example, relating the population dynamics of the species to temporal variability. For this, the otolith structures were extracted from samples of the species, captured in the study of the Buranhém River in Porto Seguro, Bahia. For processing, the otoliths were resined, sawn, manually sanded, photographed in the laboratory and added to the drive. In the analysis of the microphotographs, evident and spaced marks were detected that suggest an annual or biannual circadian pattern for the individual. In relation to the analysis of the time series of carapebas catches, from artisanal fishing with camboas, recorded for Beach in Barra Grande, Península de Maraú, Bahia, it was possible to identify a strong seasonality in the evaluated indices (CPUE, fishing days, fishermen/day, camboas/day and total landings) decreases as the group's main capture period occurs between April and July, justified by migratory behavior during the reproductive cycle, influenced by environmental factors. Furthermore, a trend of increasing effort and capture of this species was identified throughout the time series, which may indicate greater fishing pressure on this population. However, as these inferences are indirect, new studies are necessary to confirm these hypotheses.